Novel and facile method for fabrication of robust superhydrophobic film on copper surface and its chemical, mechanical, and corrosion performance. (3rd October 2021) - Mohamed, M. E.; Mahgoub, F. M.; Ragheb, D. M.; Abdel-Gaber, A.M.
ABSTRACT: Superhydrophobic films were successfully designed for a copper substrate using potentiostatic deposition of Ni and Ni-graphene composite followed by treatment with stearic acid (SA). A scanning electron microscope was used to examine the surface morphology of the prepared superhydrophobic films, and the results revealed that both Ni-SA and Ni-graphene-SA films have micro-nano structures. FTIR measurements revealed that the copper substrates had been coated with Ni-SA and Ni-graphene-SA films. The Ni-graphene-SA film has the highest chemical stability and mechanical abrasion resistance. Potentiodynamic polarization and electrochemical impedance spectroscopy results indicated that the formulated superhydrophobic films on the copper substrate have high corrosion resistance in 0.5 M NaCl.